Anticoagulant Activity and Pharmacokinetic Properties of a Sub-cutaneously Administered Mixed Micellar Formulation of Argatroban in Experimental Animals - Berry, Christopher N.; Lunven, Catherine; Lecoffre, Catherine; Lainée, Pierre; O’Connor, Stephen E.; André, Frédéric; Roger, Bénédicte; Garrigou-Gadenne, Danielle; Rouchouse, Alain; Roome, Nigel O.; Vivan, Nathalie (Thrombosis and Haemostasis, 2000)
We have studied the anticoagulant properties of a novel mixed micellar formulation containing 14 mg/ml argatroban administered by the sub-cutaneous (s. c.) route to rats, rabbits, dogs and primates. Blood samples were taken at various times post-treatment for the determination of the thrombin time (TT), Ecarin clotting time (ECT) and the activated partial thromboplastin time (aPTT). Plasma levels of argatroban were determined in the dog and primate.Mixed micelles alone (0.15 M sodium glycocholate and 0.15 M egg lecithin) were without effect on the clotting parameters. The mixed micellar formulation of argatroban dose-dependently increased all three clotting parameters in the rat (1–4 mg/kg), the rabbit (1 and 2 mg/kg), the dog (1 and 2 mg/kg) and the primate (0.25 and 0.5 mg/kg). In each case the TT was the most sensitive parameter, followed by the ECT and the aPTT. The duration of action of argatroban in each species was dose dependent and varied from 3 h in the rat to 6 h in the dog. In the latter, the mixed micelle formulation had a significantly increased plasma half-life and mean residence time without affecting the overall area under the curve. The increases in the clotting time were strongly correlated with the plasma levels of argatroban and were linear across the range of concentrations obtained in the dog and the primate, although the aPTT plasma concentration response curve was very flat. Species differences were noted between the increase in clotting time for a given plasma concentration, with the primate being more sensitive than the dog (e. g. 4.7 times more so in terms of the ECT).Thus, a mixed micellar formulation of argatroban, which markedly enhances its solubility, could be useful as a potential anticoagulant for sub-cutaneous administration.
Keywords: Argatroban mixed micelles; thrombin time; ecarin clotting time; aPTT; plasma levels